Y‐craniosynostosis by premature fusion of the metopic and coronal sutures: A new nosological entity or a variety of Saethre‐Chotzen syndrome?. Issue 4 (24th March 2015) - di Rocco, Federico; Benoit, Alexandra; Vigneron, Jacqueline; Segura, Pascale Bach; Klein, Olivier; Collet, Corinne; Arnaud, Eric
Abstract : Background: New forms and varieties of craniosynostoses are continuously identified due to the current increased interest of clinicians and genetists especially since the introduction of microarray‐based comparative genomic hybridization (Array‐CGH) techniques in the diagnostic setting of patients with craniofacial anomalies. Methods: In this report, we describe the case of an infant who associated the early fusion of the metopic and both the coronal sutures. The interaction of the early fusion of the anterior group of the main cranial sutures gave the infant a particular clinical phenotypes with a Y configuration of the frontal bone and a globally reduced size of the skull. Such a deformity was observed in utero and was subsequently confirmed by the postnatal imaging of the head. Results: This phenotype was never described previously in antenatal period to our knowledge. The array‐CGH showed a heterozygous 9.0 Mb deletion in the chromosomal region 7p21.1p21.3 encompassing approximately 25 other genes, spanning from THSD7A to TWIST1/FERD3L . Conclusion: This case further illustrates the variability of the clinical spectrum of craniofacial disorders associated with TWIST1 abnormalities. It is important to note that the Saethre‐Chotzen syndrome caused by microdeletion is generally characterized by a mental disability. However, of interest, the postoperative psychomotor development of the child considered hereby was within the normal limits. Birth Defects Research (Part A) 103:306–310, 2015. © 2015 Wiley Periodicals, Inc.